If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 13 = 6x + 202 Reorder the terms: 13 + 13x = 6x + 202 Reorder the terms: 13 + 13x = 202 + 6x Solving 13 + 13x = 202 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 13 + 13x + -6x = 202 + 6x + -6x Combine like terms: 13x + -6x = 7x 13 + 7x = 202 + 6x + -6x Combine like terms: 6x + -6x = 0 13 + 7x = 202 + 0 13 + 7x = 202 Add '-13' to each side of the equation. 13 + -13 + 7x = 202 + -13 Combine like terms: 13 + -13 = 0 0 + 7x = 202 + -13 7x = 202 + -13 Combine like terms: 202 + -13 = 189 7x = 189 Divide each side by '7'. x = 27 Simplifying x = 27
| 1=1-5m+6m | | 6(x+3)-12-4(x-3)= | | .5(6x+2)=49 | | -19.480+x=-28.03 | | 12x-6=10x+20 | | 75-5x=4x+20 | | 9x-4=-16 | | -8=4k+4k | | 25=7+-12+33k | | 10x+13=3(3x+5) | | 7(4-a)=3a-12 | | 3w^2=22W+16 | | 2x+2-4x=6(x+-2) | | 103-8x=9x+16 | | 6x-5=2x+25 | | (14w+9)(5w-15)=0 | | (x-6)(2x+7)= | | 2x+12x-18=0 | | 5x+2=4+2x+10 | | -7x-5y=35 | | (-1xy)3=(1x)*(y)3 | | 9x-84x=7x+16 | | xa-ba=12 | | -9=-5-4x | | 42m=996 | | 2(8x-3)=10x+30 | | 6(q-5)-3q=12 | | 15p^3= | | -3x+2+8x=2x+14 | | 2n+12=3n-31 | | 5y=15x-90 | | 2n-4+5=-7 |